Archive partisans: Forbidden histories and the promise of the future. (June 2019) - Hegasy, Sonja
Remembering past injustices has been regarded as central to overcoming intra-societal conflicts with the end of World War II. Since, memory has increasingly been charged as a means to achieve reconciliation. But only in recent years have archives, and here especially human rights archives, in the Mashreq and Maghreb moved from being semi-functional repositories for academics to become important loci for political activists to reappraise violence and injustice. The role of the archive in preserving or erasing personal memories is critically investigated by such activists. This article covers an emergent discourse on the memory milieus of violent conflict, war, and occupation extant in this region. In a selective overview covering Morocco, the Western Sahara, Lebanon, and Egypt, it asks what the visibility of violent experiences means for the wider social context and how traumatic pasts are re-socialized through private and public archiving initiatives. The author investigates the archive less as a place of storage than as a milieu around which various actors conceptualize the past and struggle over future justice.